The significance of vertical farming concept in ensuring food security for high-density urban areas - Kalantari, Fatemeh; Nochian, Ashkan; Darkhani, Faiza; Asif, Nayeem (UKM Press, 2020)
Cities are increasingly turning into megacities due to their enlarged and intense population. There has been a global attempt by designers to spread the view that cities can be potential areas for producing loads of food required by communities and fitted for specific ecologies. A similar trend has been spread to developing countries where it is essential to provide food for local consumption, and serious attempts are made to distribute food materials to protect particular urban communities. Therefore, recent attempts of food security have aimed not only to guarantee availability but also the provision of sustainable, locally-fitted and food production that is not industrialized to sustain the potential for production. The solution seems to be Vertical Farming (VF). Producing food can be brought into cities through VF and this significant step, if taken, can make life in cities more viable. The present research aims to review the VF plays in the future of food production in high-density cities. The present research reviews the body of related literature, both online and printed publications on the issue. VF is a turning point of the millennium in urban designing but not limited to that. It further presents a new type of architecture as both a local and global remedy for the 21st crisis.